Dinâmica da macrofaunafauna na serapilheira em áreas com plantio de Eucalyptus spp. e Caatinga, em Olho D’Água das Flores, Semiárido de Alagoas - Alves, Sherliton da Silva (2018)
Eucalyptus cultivation has been expanding in several brazilian biomes, due to its financial return and its adaptability to diverse soil and climatic conditions. The Alagoan Semiarid has become the target of a project to implant this culture, which is stated in the literature as a promoter of serious ecological problems in the environments in which it is installed. Macrofauna is considered an indicator of soil quality because it has important functions in soil/plant dynamics. Thus, the objective was to evaluate the macrofauna dynamics in a plantation of Eucalyptus spp. and in Caatinga area, under animal grazing, in the municipality of Olho D'Água das Flores, Alagoas Semiarid. Observation points in the two areas were evaluated monthly to evaluate leaf decomposition, litter accumulation, carbon and soil organic matter contents, soil water temperature and water content, and bimonthly the macrofauna. To evaluate leaf decomposition, leaves of Eucalyptus spp. were oven dried at 65 °C for 72 hours, 15,0 g in litter bags measuring 20x20 cm and installed in the area of Eucalyptus spp., totaling 120 litterbags. Each month 10 litterbags were randomly removed and the remaining material was oven dried at 65 °C for 72 hours to determine the rate of decomposition (g/month) relative to the initial weight (15,0 g). The litter accumulation was measured by means of an iron frame (50x50 cm), cast twice, near the observation points, in each experimental area and collected the material on the soil, which was done in a greenhouse at 65 °C for 72 hours, and a new weighing was performed to determine the total weight of the samples (kg ha-1). Carbon and soil organic matter contents were determined by collecting soil samples (0-10 cm) at the observation points of the areas, following the colorimetric method. The water content of the soil was recorded by means of soil samples from both areas, on the surface (0-5 cm) and subsurface (5-10 cm), packed in aluminum cans of known weight, weighing the weight humid and taken to the oven at 105 ºC for 24 hours, and then weighed for dry weight, determining the percentage of humidity. The macrofauna survey was carried out in the two areas through Provid traps, installed on the surface and subsurface of the soil and in the aerial stratum of the trees, and Aerial traps also installed in the aerial stratum of the trees. The traps were kept in the field for 96 hours containing 200 mL of 5% detergent solution and 12 drops of Formol P. A. The organisms caught ≥ 2 mm were quantified and identified at the level of taxonomic group. The Hymenoptera group is the most dominant in the areas of Eucalyptus spp. and Caatinga, regardless of the type of trap, confirmed by the low values in the Shannon (H) and Pielou (e) Uniformity Indices. Regardless of the areas, abundance is higher in the drought period, attributed to the dominance of this group, and the richness of taxonomic groups is higher in the rainy season. The accumulated litter, independent of the areas, occurred higher during the dry season, and presented higher values in the area of Eucalyptus spp. The structural components present in leaf material such as low Nitrogen content, high C:N ratio and high lignin content influence the low decomposition of Eucalyptus spp., However, the main regulating factor of this process in the experimental period is rainfall which remained above the historical average, accelerating the loss of mass, favoring the presence of decomposing organisms. The highest levels of carbon and soil organic matter are verified in the Caatinga environment, demonstrating that this area is in a better equilibrium condition, favored by soil organisms, responsible for the nutrient cycling process.